Huntington's Disease: Two-Year Observational Follow-Up of Executive Function Evaluation with CNS Vital Signs Test in an Adult Patient - Anna Lucia Spear King; Alexandre Martins Valença; Adriana Cardoso de Oliveira e Silva; Ana Claudia Cerqueira; Lígia Maria Chaves Ferraz; Antonio Egidio Nardi (Case Reports in Medicine)
Huntington's disease (HD) is a genetic, degenerative, and progressive central nervous system disease. It is characterized by motor abnormalities and cognitive and psychiatric symptoms. Objective. To describe the precise degree of clinical severity of patients with HD through a new neurocognitive assessment. Methods. Unprecedented battery of computerized tests, CNSVS (Central Nervous System Vital Signs), was applied at three different moments in 2008, 2009, and 2010. The accurate and reliable CNSVS objectively provided the cognitive state of patients and allowed for the evaluation of disease progression. Case Report. P., 26, female, without any medication, with normal psychomotor development is a parent carrier of HD. In 2008, she was diagnosed with HD in accordance with the Medical Genetics Laboratories. Conclusion. The tests may be useful to reveal the exact measure of the current evolutionary stage of HD patients, allowing for more efficient planning of treatment and future procedures, such as the medication, therapy, and physical activity to be administered.